"You don’t get side effects from social prescribing”— a qualitative study exploring community pharmacists’ attitudes to social prescribing - Rathbone, AP; Pearson, H; Akinyemi, O; Cartwright, N; Tierney, S; Rowlands, G; Lindsey, L (Public Library of Science, 2024)
Objectives: Social prescribing is an approach that enables the referral of patients to non-clinical support and places a focus on holistic care. This study explored views of community pharmacists regarding social prescribing in pharmacies. Study design: A qualitative phenomenological approach was used. Methods: A convenience sample of eleven community pharmacists from Northern England were recruited via social media (Twitter, Facebook) and took part in a semi-structured, one-to-one qualitative interviews that asked about their knowledge of social prescribing, the advantages of community pharmacist involvement and any barriers they predicted to its implementation. Interviews were transcribed verbatim and thematically analysed. Results: The sample included largely male pharmacists (63.3%) with less than five years’ experience (45.5%) and included pharmacists working as employees (63.6%), locums (27.3%) and owners (9%) in both chain (36%) and independent stores (54.5%). The main findings indicate an enthusiasm for but limited understanding of social prescribing. Factors which appeared to influence involvement were training requirements and time available to complete an additional service in busy pharmacies. Opportunities centred on the broader pharmacy team’s role to optimise health outcomes. Conclusions: The findings indicate pharmacists may be an underused resource due to a poor understanding of the full scale and scope of social prescribing beyond health promotion, lifestyle interventions. Further work is needed to explore the transferability of the findings to the broader pharmacy workforce to understand how social prescribing can be positioned within pharmacy practice.